Effectiveness of Social Media Marketing Practices (SMMP) for Freelance Trainers, Coaches, and Learning & Development Professionals in India - Kumar, Amitabh (Digital Repository of Theses - SSBM Geneva, 2025)
In the rapidly evolving digital ecosystem, freelance trainers, coaches, and learning and development (L&D) professionals in India are increasingly reliant on Social Media Marketing Practices (SMMP) to expand their client base and enhance brand visibility. This abstract detail the outcomes of a comprehensive study aimed at identifying the most effective content types and engagement strategies on social media that contribute to increased client inquiries and brand visibility for these freelancers. The research utilized a robust mixed-methods approach, engaging with over 225 freelance trainers, coaches, and learning and development (L&D) professionals in India who are using social media across various platforms including LinkedIn, Facebook, Instagram, X, Youtube etc. The study meticulously analyzed the effectiveness of different content types such as posts, educational articles, motivational quotes, video tutorials and live interactive sessions. It also examined engagement strategies like posting frequency, real-time interaction with followers, and strategic use of hashtags and partnerships. Our findings indicate a clear superiority of video content over other types - video tutorials and live broadcasts consistently yielded the highest engagement rates, shares, and comments, significantly boosting user interaction and visibility. Interactive content such as Q&A sessions and polls also proved highly effective, facilitating enhanced engagement by encouraging audience participation and fostering a community feeling. In terms of engagement strategies, our analysis revealed that freelancers who maintained a regular posting schedule and engaged directly with their audience through prompt replies and personalized interactions experienced a marked increase in follower loyalty and client inquiries. Moreover, the strategic use of relevant hashtags and collaboration with other industry influencers expanded their reach and visibility, penetrating new demographic segments more effectively. The research conclusively demonstrates that a strategic approach to social media, emphasizing video and interactive content coupled with consistent and personal engagement, can substantially improve the visibility and client engagement for freelance trainers, coaches and learning and development professionals in India. Implementing these focused strategies can lead freelance trainers, coaches and learning and development (L&D) professionals to achieve greater market presence and business growth in the competitive landscape of Social Media Marketing Practices (SMMP) for professional training and coaching services.